ANALISIS KEIMANAN MAHASISWA MELALUI PENDIDIKAN AGAMA ISLAM DALAM KONTEKS GLOBALISASI BUDAYA - Rahmah, Khalida (Institut Agama Islam Negeri (IAIN) Bone, 2025)
The K-Pop phenomenon has become part of global popular culture, including in Indonesia. The music, dance, fashion, and lifestyle introduced by K-Pop idols are widely followed by their fans, especially among teenagers and students. In Islam, idolizing someone is allowed, but with clear limitations. This study aims to see the extent of K-Pop's influence on the faith aspects of Muslim students who are fans of K-Pop, and how they are influenced by K-Pop. This study uses a quantitative descriptive approach and survey method to analyze the faith of Muslim students at Medan State University who are fans of K-Pop. The population in this study were Muslim students who were fans of K-Pop. The sample of this study was 25 Muslim students who met the criteria as K-Pop fans. The majority of respondents have a fairly good level of awareness in practicing Islamic teachings in their daily lives. Most respondents routinely perform the five daily prayers, maintain relationships according to Islamic teachings, and try to prioritize Islamic values in their lives. However, there are still some individuals who are not fully consistent in carrying out their worship and need to get further motivation and education to be more consistent in carrying out their religious obligations.